Avaliação do método de preparo cavitário na integridade marginal e resistência de união de sistemas adesivos à dentina humana - Barros, Lívia de Oliveira (2015)
Smear layer (SL) is an amorphous layer of organic and inorganic debris formed on the surface of dentin after mechanical preparation of a cavity with rotating or manual instruments. The cavity preparation method and micromorphological characteristcs of SL and underlying dentin surface, might affect the adhesive performance. The current study is divided in two chapters, whose aims: 1) To evaluate the effect of dentin surface preparation method on micromorphological characteristics of dentin surface and on the microtensile bond strength (μTBS) of two adhesive systems to dentin. (Chapter 1); 2) To evaluate the effect of cavity preparation method on marginal integrity and sealing ability of resin-tooth interface produced by two adhesive systems (Chapter 2). Standardized class I cavities (5 x 4 x 3 mm), with margins in enamel, were prepared in sound extracted human molars, according to the preparation method (n=20): (1) Medium grit diamond bur; (2) Medium grit diamond bur followed by extra-fine grit diamond bur; (3) 12 blades Tungsten carbide bur and (4) 12 blades Tungsten carbide bur followed by 30 blades Tungsten carbide bur. Composite restorations were inserted in cavities after AdperTM ScotchbondTM Multipurpose (SBMP) or ClearfilTM SE Bond (CSE) application. Epoxy replicas of restorations were obtained after 20,000 thermo-mechanical cycles. Resin-dentin bonded sticks were prepared for μTBS testing, pulled until failure at crosshead speed of 0.5 mm/min and failure pattern was evaluated (Chapter 1). For evaluated of restorations marginal integrity, epoxy replicas were observed under scanning electron microscope (SEM) to analysis of the percentage of gap-free margins (Chapter 2). Additional teeth (n=16) were prepared using same groups tested and investigated by SEM to micromorphological qualitative analysis of dentin surface and SL characteristics (Chapter 1). Extra teeth (n=48) were prepared, restored and then immersed in 2% methylene blue for dye penetration analysis (Chapter 2). Under SEM analysis, medium grit diamond bur produced thicker SL and more irregular dentin surface than Tungsten carbide burs. SBMP adhesive yielded the highest μTBS when medium grit diamond bur was used and for CSE 30 blades Tungsten carbide bur group showed the highest values (p<0.05) (Chapter 1). Cavity preparation methods did not affect the percentage of gap-free margins and dye penetration for SBMP (p>0.05). CSE exhibited the highest percentage of gap-free margins and lowest dye penetration when medium grit diamond bur was used (p<0.05) (Chapter 2). Dentin surface preparation 24 method affected SL characteristics, dentin surface topography, subsequently, resin- dentin bond strengths. Dentin surface irregularity was able to improve resin-dentin bond performance for SBMP. SL thickness and irregularity may compromise bonding efficacy of the self-etching system. The influence of the cavity preparation method on the marginal integrity and sealing ability were dependent of the adhesive used, once it affected more the performance of self-etching adhesive.